Diabetic kidney disease: a clinical update from Kidney Disease: Improving Global Outcomes - Molitch, Mark E.; Adler, Amanda I.; Flyvbjerg, Allan; Nelson, Robert G.; So, Wing-Yee; Wanner, Christoph; Kasiske, Bertram L.; Wheeler, David C.; de Zeeuw, Dick; Mogensen, Carl E. (Kidney international, 2015)
The incidence and prevalence of diabetes mellitus (DM) continue to grow markedly throughout the world, due primarily to the increase in type 2 DM (T2DM). Although improvements in DM and hypertension management have reduced the proportion of diabetic individuals who develop chronic kidney disease (CKD) and progress to end-stage renal disease (ESRD), the sheer increase in people developing DM will have a major impact on dialysis and transplant needs. This KDIGO conference addressed a number of controversial areas in the management of DM patients with CKD, including aspects of screening for CKD with measurements of albuminuria and estimated glomerular filtration rate (eGFR); defining treatment outcomes; glycemic management in both those developing CKD and those with ESRD; hypertension goals and management, including blockers of the renin–angiotensin–aldosterone system; and lipid management.